A Two‐Stroke, Two‐Cylinder Piston Rotaxane Motor. Issue 12 (22nd March 2016) - Sevick, Edith M.; Williams, David R. M.
Abstract: We introduce a model for a rotaxane motor. This uses two major themes of rotaxane physics, that is, the ability to change the potential of different regions of the axle (switching) and the entropy associated with free rings. The motor is based on free rings being trapped and released by potential stripes or stations. We calculate the power produced by such a motor, which is in the femtoWatt range. The power is proportional to the square of the number of rings. Abstract : Firing on all cylinders : A model for a rotaxane motor is discussed. The crucial elements are the coupling of ring entropy with stations that can be switched on and off. What happens when the power output is dissipated by viscous drag on the piston ring? This power output depends on the response of the piston ring, and it is shown that the power output varies inversely to the drag constant for the ring. However, the power output can be utilised in different ways, such as to generate elastic or kinetic energy.